Bioprotein Production from Agricultural Waste and Cheaper Carbon Source: Fulfilling the Hope of Millions - Jamal, Parveen; Tompang, Mohamad Fahrurrazi; Alam, Md. Zahangir; Abdul Karim, Mohamed Ismail; Salleh, Hamzah Mohd. (2010)
The necessity for exploring unconventional, non-agricultural means of food production, especially of proteins, has created a demand for the formulation of innovative and alternative protein rich food sources having a high nutritional value which are non competitive with food for human consumption, economically feasible and locally available. Thus, the production of bioproteins (proteins derived from micro-organisms) by fermentation of agricultural waste products is one of the most promising approaches of biotechnological innovations for increasing the availability of proteins. In addition to high quality, quantity will be more comparable to farm animals due to rapid growth rate of microorganisms and high production of bioproteins. Due to the increasing demand for bioproteins, the efficient strains, substrate and method must be used for high yield product. Moreover, increasing concern about pollution that occurs from agricultural and industrial waste has stimulated interest in converting waste materials into commercially valuable products. Therefore, this study emphasized on microbiological transformation of pineapple waste, which contains valuable components like sucrose, glucose, fructose and other nutrients. Phanerochaete chrysosporium PC-13(PC2094) was used as potential strain after screening various microorganism and agricultural wastes.